2018
DOI: 10.1093/ofid/ofy106
|View full text |Cite
|
Sign up to set email alerts
|

Improving Aztreonam Stewardship and Cost Through a Penicillin Allergy Testing Clinical Guideline

Abstract: BackgroundPatients reporting penicillin allergy often receive unnecessary and costly broad-spectrum alternatives such as aztreonam with negative consequences. Penicillin allergy testing improves antimicrobial therapy but is not broadly used in hospitals due to insufficient testing resources and short-term expenses. We describe a clinical decision support (CDS) tool promoting pharmacist-administered penicillin allergy testing in patients receiving aztreonam and its benefits toward antimicrobial stewardship and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…An overview of the characteristics of the included studies is listed in Table 2. Generally, twenty-two studies (81%) [5,[13][14][15][16]18,[20][21][22][23][24][25][28][29][30][31]32,[34][35][36][37][38] out of the included twenty-seven studies report cost savings after implementing an EHR based CDS intervention. Four studies (15%) [17,26,27,33] report a rise in cost expenditure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An overview of the characteristics of the included studies is listed in Table 2. Generally, twenty-two studies (81%) [5,[13][14][15][16]18,[20][21][22][23][24][25][28][29][30][31]32,[34][35][36][37][38] out of the included twenty-seven studies report cost savings after implementing an EHR based CDS intervention. Four studies (15%) [17,26,27,33] report a rise in cost expenditure.…”
Section: Resultsmentioning
confidence: 99%
“…In the majority of included studies the main cost outcome measures were related to laboratory test cost. [15][16][17]20,21,25,28,29,31,32,38] Exploration of different front-end CDS intervention categories According to the taxonomy by Wright et al [12], we identi ed ten (37%) studies [5,13,15,20,22,23,26,[36][37][38] which explored EHR based CDS interventions based on point-of-care alerts or reminders (category 3). Three interventions (11%) [17,27,34] were order facilitators (category 2).…”
Section: Resultsmentioning
confidence: 99%
“…The most common single antibiotic targeted for reduction was aztreonam. 21,23,25,27,28,46,48 Other targeted antibiotics included carbapenems, vancomycin, linezolid, tigecycline, daptomycin, and moxifloxacin. 22,30,[32][33][34][35]46,49 Targeting Infections One PST-based pathway relied on reviews of each patient's infection and antibiotic data to select patients that would likely have a therapy change with a negative PST.…”
Section: Patient Selection Targeting Antibioticsmentioning
confidence: 99%
“…34,40 Some PST pathways excluded patients with recent type I reaction or anaphylaxis history. 38,48 Other PST-based pathway exclusions included cutaneous conditions, severe cardiac or pulmonary comorbidities, immunosuppression, pregnancy, altered mental status, and clinical instability. 31,37,48 Implementation Teams Implementation teams were often multidisciplinary with diverse perspectives and varied expertise.…”
Section: Targeting Patientsmentioning
confidence: 99%
“…Several strategies have been developed and reported in the literature to attempt to decrease the inappropriate labeling of BL allergies and subsequent avoidance of BL therapy including penicillin skin testing, decision support tools for patients with documented penicillin allergies, and pharmacist-driven BL allergy interviews. [9][10][11][12][13][14] In a recent study, patients who received skin testing per hospital protocol and who were subsequently treated after provider utilization of a computerized guideline application with clinical decision support were 5.7 and 1.8 times more likely to receive a penicillin or cephalosporin, respectively. 14 A pilot-study of a standardized BL allergy questionnaire used by pharmacists found that 63% of assessed patients had previously tolerated a BL antibiotic resulting in BL prescriptions for 87.5% of the 24 patients deemed eligible for BL therapy.…”
mentioning
confidence: 99%